A beta subunit mutation disrupting the catalytic function of Escherichia coli RNA polymerase. - Lee, J (1991)
The substitution of the evolutionarily conserved Glu-813 for lysine in the beta subunit of RNA polymerase (RNAP) causes a partial loss of function in the assembled RNAP. In the presence of the four ribonucleoside triphosphates, the mutant RNAP displayed a decreased frequency of promoter clearance and diminished elongation rate. Both defects could be compensated by raising the ribonucleoside triphosphate concentration. In the abortive initiation reaction limited by the incomplete set of ribonucleoside triphosphates, the mutant RNAP generated aberrant patterns of products indicative of their enhanced loss from the RNAP-promoter complex. A model is proposed, attributing the multiple effect of the mutation to the malfunctioning of the RNAP active center.